The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2174/1874613601206010213
|View full text |Cite
|
Sign up to set email alerts
|

Use of and Adherence to Antiretroviral Therapy in a Large U.S. Sample of HIV-infected Adults in Care, 2007-2008

Abstract: Background:Antiretroviral therapy (ART) is the cornerstone of HIV clinical care and is increasingly recognized as a key component of HIV prevention. However, the benefits of ART can be realized only if HIV-infected persons maintain high levels of adherence.Methods:We present interview data (collected from June 2007 through September 2008) from a national HIV surveillance system in the United States—the Medical Monitoring Project (MMP)—to describe persons taking ART. We used multivariate logistic regression to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…Given that ARV medication is the cornerstone of any successful HIV program (Gallant et al, 2011), having PHAs access lifesaving ARV treatment in a timely manner optimizes their quality of life and avoids possible complications (Beer et al, 2012). This approach is in addition to meeting other requirements such as socioeconomic and psychological needs (UNAIDS, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Given that ARV medication is the cornerstone of any successful HIV program (Gallant et al, 2011), having PHAs access lifesaving ARV treatment in a timely manner optimizes their quality of life and avoids possible complications (Beer et al, 2012). This approach is in addition to meeting other requirements such as socioeconomic and psychological needs (UNAIDS, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1821 Examinations of the prevalence and predictors of ART discontinuation have demonstrated that certain patients are more likely to discontinue ART. Substance use, 22 injection drug use, 23 disease severity, 14,22,24,25 younger age, 14,25,26 racial/ethnic minorities, 26,27 female gender, 22,28 unemployment, 28 perceived HIV stigma, 29 fear of discrimination, 30 mental health, 14,24,28,31,32 and side effects 33 have been associated with ART discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances in the pharmacological properties of antiretroviral therapy (ART) have resulted in decreased side effects and once-daily pill-taking options, significantly reducing treatment burden. Despite these improvements, treatment adherence and retention remain a chronic problem for some people living with HIV (PLWH; Beer et al, 2012; Castro, Santiago, Jiménez, Dávila-Vargas, & Rosal, 2015). …”
mentioning
confidence: 99%